Sistem Skoring Diagnosis Fibrilasi Atrium pada Kasus Stroke Iskemik - Erick Hoetama; Bambang Hermawan Hermawan; I Gusti Made Sunia (The Indonesian Heart Association, 2016)
Background & Objectives. Atrial Fibrillation (AF) is the most common arrhytmia that is found in daily practices. Patients with AF have four- to five-fold increased risk of developing ischemic stroke compared to normal population. Diagnosing AF can sometimes be quite difficult especially in the setting of paroxysmal AF. Moreover, paroxysmal AF can also increase the risk of thromboembolic complications. Some cases of cryptogenic stroke are believed to be cardioembolic in origin which caused by occult AF. This study aimed to develop a simple scoring system to detect patients with ischemic stroke most likely to have AF, so that recurrent stroke can be prevented.Methods. We conducted diagnostic study using cross sectional design. Total 173 subjects were gathered. Those subject were patients with ischemic stroke admitted in Belitung or Ruteng General Hospital from January 2014 until August 2015. Data collected were subjects’ characteristics, hypertension, diabetes, obesity, dyslipidemia, smoking history, congestive heart failure (CHF), alcohol consumption, valvular heart disease, chronic obstructive pulmonary disease, myocardial infarct history, previous stroke, Modified National Institutes of Health Stroke Scale (mNIHSS) score, and left atrial diameter (LAD). We analyzed those data using bivariate and logistic regression multivariate analysis.Results. Multivariate analysis showed significant relationship between AF and some of the variables, which are hypertension, diabetes, obesity, CHF, left atrial enlargement, age and mNHISS score. We developed 7-point scoring system derived from those variables. A cutoff score of 3 or higher has sensitivity 97,1% and specificity 54,3%. Also, this scoring system has Area Under the Curve (AUC) value of 88,9% (IK95% 83,1% - 94,7%).Conclusion. This scoring system uses only clinical and echocardiographic profile that are easy to do, so it can be utilized as a simple diagnostic tool to identify ischemic stroke patient who is likely to have AF. Future studies are needed to determine another possibly related parameters.